EVALUATING FIRST-LINE ANTIMICROBIAL PRESCRIBING PRACTICES: A PRE- AND POST-TEST ANALYSIS TO MITIGATE ANTIBIOTIC MISUSE - Sunil Saundankar; Ram Bhajan Kumavat (South Eastern European Journal of Public Health, 2025)
Antimicrobial resistance (AMR) is one of the most critical global health challenges, threatening the efficacy of antibiotics and contributing to increased morbidity, mortality, and economic burdens. The misuse of broad-spectrum antibiotics as first-line treatments, often in cases where narrow-spectrum alternatives suffice, is a significant driver of AMR. Factors such as poor adherence to prescribing guidelines, diagnostic uncertainty, and lack of awareness among healthcare professionals exacerbate the issue. This study aimed to evaluate the impact of targeted educational interventions on first-line antimicrobial prescribing practices in Nashik City, Maharashtra. A pre- and post-test design was employed with a stratified sample of 228 medical practitioners, including allopathic, Ayurvedic, and specialist practitioners. Participants completed a structured pre-test questionnaire assessing their prescribing practices, awareness, and adherence to guidelines. Following this, they were exposed to communication materials emphasizing rational antibiotic use, risks associated with AMR, and the role of diagnostics. Post-test responses were analyzed to assess the intervention's effectiveness. The results showed significant improvements in practitioners’ adherence to guidelines, prioritization of diagnostic tools, and awareness of antimicrobial stewardship. Awareness about AMR rose from 78.5% pre-test to 91.22% post-test, while the recognition of rapid culture and sensitivity tests increased from 78.07% to 93.28%. Furthermore, regulatory and systemic measures, such as restricting over-the-counter antibiotic sales, saw increased emphasis post-intervention. In conclusion, this study demonstrates the effectiveness of targeted educational interventions in improving prescribing behaviors and addressing the multifaceted challenges of AMR. The findings emphasize the need for continuous education, enhanced diagnostic infrastructure, and policy-level reforms to mitigate antibiotic misuse and combat AMR sustainably.